2014
DOI: 10.1111/1471-0528.12684
|View full text |Cite
|
Sign up to set email alerts
|

The impact of obesity on outcomes of midwife‐led pregnancy and childbirth in a primary care population: a prospective cohort study

Abstract: Objective To assess the impact of obesity on the likelihood of remaining in midwife-led care throughout pregnancy and childbirth.Design Secondary analysis of data from a prospective cohort study.Setting Dutch midwife-led practices.Population A cohort of 1369 women eligible for midwife-led care after their first antenatal visit.Methods First-trimester body mass index (BMI) was calculated as weight measured at booking divided by height squared. Obstetric data were retrieved from medical records. Multiple logisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
(93 reference statements)
0
6
0
Order By: Relevance
“…For example, recent research suggests that otherwise healthy parous women with a BMI of 35–40 kg/m 2 may have relatively low intrapartum risks, 21 and a Dutch study found that extremely obese women achieved good outcomes in midwifery-led care. 22 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, recent research suggests that otherwise healthy parous women with a BMI of 35–40 kg/m 2 may have relatively low intrapartum risks, 21 and a Dutch study found that extremely obese women achieved good outcomes in midwifery-led care. 22 …”
Section: Discussionmentioning
confidence: 99%
“…Further research is required into whether some groups of ‘higher risk’ women might be safely looked after in other midwifery‐led settings. For example, recent research suggests that otherwise healthy parous women with a BMI of 35–40 kg/m 2 may have relatively low intrapartum risks, and a Dutch study found that extremely obese women achieved good outcomes in midwifery‐led care …”
Section: Discussionmentioning
confidence: 99%
“…Obesity was introduced in the vignettes because this characteristic challenges midwives’ clinical decision-making on medical and psychosocial levels. Obese women experience stigma, which may threaten the bond of trust between midwife and woman [ 19 ] and in the Netherlands, there is scant evidence on the best care for obese women in midwife-led care, clear national guidelines are lacking, and local protocols are ambiguous [ 20 ]. Based on discussions with practising midwives (other than the ones interviewed), we identified typical clinical dilemmas associated with supporting obese women and incorporated these in the vignettes.…”
Section: Methodsmentioning
confidence: 99%
“…[4][5][6][7] The progression of the birth process and concomitant interventions are associated with maternal characteristics such as age, parity, body mass index (BMI), ethnicity, illness and infant birth weight, as well as with organisational factors such as existing guidelines, the availability of 24 hours pain relief, the profession of the obstetric care provider (midwife vs physician) and the level of care (primary/secondary). [8][9][10][11][12] Moreover, maternal anxiety might play a role in the birth process. Although one review found no overall association between anxiety and obstetric complications, specific types of anxiety (such as fear of childbirth) may be Possible relationship between general and pregnancy-related anxiety during the first half of pregnancy and the birth process: a prospective cohort study Johanna Maria Koelewijn, 1,2 Anne Marie Sluijs, 3 Open Access associated with specific complications and interventions, such as prolonged labour and caesarean section.…”
Section: Introductionmentioning
confidence: 99%